Analysis of Financial and Economic Aspects of Company Functioning and Their Influence on the Tourist Cluster - YELCHIBAYEVA, Adeliya; RYSKULOVA, Alma-Gul; BAIMURATOVA, Mayrash; KAPANOVA, Gulnara; SHARIPOVA, Gulnazym; MAKSUTOVA, Ainura (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
In their management activities, many companies need to find effective solutions for forecasting and planning various scenarios for their financial activities. In this regard, effective management of the financial activities of large enterprises should be based on the continuous improvement of business processes, where it is necessary to take into account the circumstances of the enterprise and increase its competitiveness through the consistent application of optimization processes and their objective assessment using methods of forecasting and planning financial activities. The purpose of the study is to analyze the financial and economic aspects of the functioning of companies and their influence on the tourism cluster in the context of the socialization of society.